AMELIORATION OF NECROSIS FORMATION IN GINGIVA BY LICORICE ROOT EXTRACT - Ss, Shivanni; V, Vishnu Priya; R, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Gingivitis is a reversible condition associated with a bacterial plaque that resolves in about 1 week after the reinstitution of oral hygiene procedures. If left untreated, may ultimately progress to periodontitis in a subset of individuals. The objective of the study was to evaluate the amelioration of necrosis formation in gingiva by Licorice root extract. The licorice compounds, licoricidin, and licorisoflavan A were the most effective antibacterial substances. Methods: Licorice root extract was prepared by macerating 50 g of dry powder with 100 ml of 70% (w/v) ethyl alcohol for a week. Human gingival fibroblasts were obtained from a commercial source and were maintained in serum-free fibroblast medium as recommended by the manufacturer. The cells were treated with licorice root extract (100 Î¼g/ml) and incubated for 48 h. Tumor necrosis factor (TNF) and C-reactive protein (CRP) were estimated. Result: TNF-alpha levels were raised, and agglutination of CRP was observed in hepatocyte growth factor positive samples whereas after the treatment with licorice root extract the TNF-alpha levels were declined and no agglutination was seen. Conclusion: TNF and CRP levels are raised during necrosis formation. These levels are decreased when treated with licorice root extract. Thus, licorice root extract causes amelioration of necrosis formation in the gingiva.